PENDIDIK KRISTEN PROFESIONAL, INSPIRATIF DAN MENARIK - Jannes Eduard Sirait (Program Studi Pendidikan Agama Kristen, 2016)
All people, including educators and teachers who are assigned to perform the duties and responsibilities of educating, were created on purpose and was provided with special gifts to fulfill God’s mandate, Christian Educators, covering the teachers and lecturers who believe that Jesus Christ is Lord and Savior are responsible for the teaching of God and doing His words. That is why educators play a significant role and determine the continuity of education and learning. Educators are educational designers, implementers, assessors and a source of inspiration to learn as well. Thus, it is a must for Christian educators to be professional, inspiring and interesting in carrying out their duties. To realize it, they must optimally equip themselves with educational science. They should also keep on learning to develop their teaching skills and knowledge. By doing so, they will be capable and reliable in carrying out their duties and responsibilities consistently. Being capable of creating and designing various learning models, they will be professional, inspiring and interesting. Abstrak: Semua manusia dicipta dan pasti menerima karunia khusus dari Tuhan untuk melakukan Amanat-Nya, salah satunya adalah menjadi pendidik dan pengajar. Pendidik Kristen yang dimaksud dalam tulisan ini adalah guru dan dosen yang beragama Kristen serta bersahadat pada iman bahwa Tuhan Yesus Kristus adalah Tuhan dan Juruselamat. Mereka bertanggung jawab mengajarkan ajaran Tuhan dan melakukan kebenaran Allah.Itu sebabnya, komponen pendidik dalam pendidikan adalah penentu keberlangsungan pendidikan dan pembelajaran. Mereka adalah desainer pendidikan, pelaksana dan penilai serta sumber inspirasi belajar. Maka, pendidik Kristen dalam melakukan tugasnya dapat dipastikan harus profesional, inspiratif dan menarik. Sebab mereka sebelumnya telah membekali diri dalam ilmu kependidikan. Pembekalan diri tersebut menjadikan mereka mampu dan handal dalam melaksanakan tugas dan tanggung jawabnya secara konsisten. Kemampuannya mencipta dan medesain berbagai model pembelajaran akan menjadikan dirinya profesional, inspiratif dan menarik.